Can Religion and Philosophy Shape the Consciousness of Values Reflecting Social Solidarity? - Gafarov, Anar (Scholarya Demo Journal of Ruby, 2018)
The present article discusses the values of social solidarity from a religious and philosophical point of view. In this sense, the approaches of religious and philosophical doctrines, as well as the views of Western philosophers, especially Islamic philosophers, are analyzed in the paper. Thus, the issue of values that ensure social solidarity, and the possibility of forming a consciousness associated with them, was discussed comparatively in the context of Islamic philosophy, especially Islamic morality. The current problems of values concerning social solidarity, factors affecting them, possible bases for building key principles, the place and significance of philosophical and theological thought in this direction will be discussed in the context of primary and secondary sources of Islamic philosophy from Farabi to Tashkoprizade.The present article analyzes philosophers’ views on values that provide social solidarity in the teleological aspect and assesses the findings analytically and synthetically on the basis of historical examples.